Minimum required angular resolution of smartphone displays for the human visual system. Issue 8 (8th October 2013) - Spencer, Lee; Jakobsen, Martin; Shah, Sunay; Cairns, Graham
Abstract There has been a rapid increase in the resolution of small‐sized and medium‐sized displays. This study determines an upper discernible limit for display resolution. A range of resolutions varying from 254–1016 PPI were evaluated using simulated display by 49 subjects at 300 mm viewing distance. The results of the study conclusively show that users can discriminate between 339 and 508 PPI and in many cases between 508 and 1016 PPI.